Jurnalisme sebagai Arena Pertarungan Kepentingan: Telaah Teori Kebudayaan - Amirudin Amirudin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
This paper is a theoretical study of the use of cultural theory which played to explain journalism activities that just not an activity to provide accurate information in the public space. In an industrial context, in fact journalism activities has face  any complex situasion. Now, the activities is no longer exclusively owned by journalists, but journalism  is a kind of football arena that have some interest in it. To present news, journalists must be able to absorb various interest from various trajectories. There is a game metaphor that journalists must follow, and how journalist do "practice" the game in the field of contestation, which will be explored using Bourdieu's cultural theory,Through this article, I hope, it can contribute to how anthropology plays a role in developing media studies, and vice versa, it can be a trigger for how anthropologists should begin to enter cultural studies which are not just exotic and simple social units; but also entered the study arena into more complex social units, for example in media organizations